Kerangka Pengembangan dan Kepemimpinan Budaya Mutu dalam Konstruksi di Indonesia: Tinjauan Studi Literatur - Peli, Martalius; Ariani, Vivi; Khadavi, Khadavi; Roza, Fielda (Jurnal Talenta Sipil, 2024)
Leadership is an indispensable element in the process of initiating and maintaining the development of a quality culture in a construction organization. Leadership can create an appropriate environment to provide maximum comfort to group members to improve performance and productivity. Strong leadership from top management is essential in developing and maintaining a quality-based culture in an organization that acts as a catalyst for the implementation of Total Quality Management (TQM). This paper aims to discuss the conceptual framework of how leadership can help change the quality culture in an organization. The discussion was carried out using a literature review of the concepts of Quality, Culture and Leadership and Organizational Culture. Analysis of the study was carried out on cultural changes and the role of leadership in developing a quality culture. The results of the study show that organizations need to shift from their current culture to a TQM culture that focuses on quality as the main strategy. Furthermore, thirteen important cultural dimensions can be identified that contribute to the successful implementation of TQM, where most of these dimensions are related to leadership. The proposed Quality Culture Development and Leadership Framework in Construction in Indonesia can be a model for developing a quality culture in construction organizations through effective leadership, so that construction organizations can use it creatively to minimize inconsistencies and conflicts.